IMPROVING STUDENT'S READING COMPREHENSION OF NARRATIVE TEXT THROUGH WHATSAPP GROUPS - Yeni Afriyeni; Gunaldi Masbiran (Universitas Pahlawan Tuanku Tambusai, 2021)
The objective of this research was to improve students’ reading comprehension of narrative text through WhatsApp. Related to the purpose of the research, the researcher design which used in this study was class action research. The subject of the research was students of class X at SMA IT Fadhilah Pekanbaru which consist of 23 students. The action research was conducted from December to January 2020 - 2021. The researcher conducted one cycle, one cycle consisted two meeting of action research. The result of the study showed that the criteria of success of this research depend on the minimum score of the school that have been determined. It was 2,66 and the research would be successful if in the class there were 75% of the students have passed minimum score. Based on the result in the cycle, it was found that 28 or 85% students succeeded. Therefore, it can be concluded that students’ reading comprehension of narrative text can be improved through WhatsApp media